Representasi Etika Asesmen Psikologi dalam Praktik Bimbingan dan Konseling pada Dinamika Pendidikan Indonesia (International Forum of Researchers and Lecturers, 2025)
Psychological assessment in guidance and counseling (GC) plays a vital role in understanding students holistically. However, its implementation in schools often faces ethical and legal challenges, particularly concerning the authority and competence of school counselors. This article examines the ethical representation of psychological assessments conducted by GC teachers through a literature review. Findings reveal that many practices exceed legal boundaries and highlight the need for professional collaboration, assessment training, and ethical literacy. Ethical assessment is not merely procedural compliance, but a form of professional responsibility to protect students’ rights and ensure accurate and safe services.